2015
DOI: 10.1111/gwao.12115
|View full text |Cite
|
Sign up to set email alerts
|

Gender as Symbolic Capital and Violence: The Case of Corporate Elites in Turkey

Abstract: Based on a Bourdieusian approach, drawing on qualitative analyses of 63 life interviews, our study demonstrates that gender is performed as both symbolic capital and violence by corporate elites within the dominant ideologies of patriarchy and family in Turkey. Our analysis reveals that, in the male-dominated context of Turkey, female elites appear to favour male alliances as a tactical move in order to acquire and maintain status in their organizations, whereas male elites appear to remain blind to the privil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 56 publications
0
25
0
1
Order By: Relevance
“…(Male, Head of Administration)Cultural fit has been argued to reproduce power relations and inequalities, for example, Doyle, Goldberg, Srivastava, and Frank () found that new employees changed their linguistic style over time to fit into their new organization. Symbolic capital may offer an explanation for the proportionally fewer women in senior management roles in general (Ossenkop, Vinkenburg, Jansen, & Ghorashi, ; Yamak, Ergur, Özbilgin, & Alakavuklar, ). Women professional staff in universities are not reported to have any less social capital than men (Sagas & Cunningham, ), and up to ‘middle management’ women have no less economic capital than men (Equality Challenge Unit, ).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Male, Head of Administration)Cultural fit has been argued to reproduce power relations and inequalities, for example, Doyle, Goldberg, Srivastava, and Frank () found that new employees changed their linguistic style over time to fit into their new organization. Symbolic capital may offer an explanation for the proportionally fewer women in senior management roles in general (Ossenkop, Vinkenburg, Jansen, & Ghorashi, ; Yamak, Ergur, Özbilgin, & Alakavuklar, ). Women professional staff in universities are not reported to have any less social capital than men (Sagas & Cunningham, ), and up to ‘middle management’ women have no less economic capital than men (Equality Challenge Unit, ).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Symbolic capital may offer an explanation for the proportionally fewer women in senior management roles in general (Ossenkop, Vinkenburg, Jansen, & Ghorashi, 2015;Yamak, Ergur, Özbilgin, & Alakavuklar, 2016). Women professional staff in universities are not reported to have any less social capital than men (Sagas & Cunningham, 2004), and up to 'middle management' women have no less economic capital than men (Equality Challenge Unit, 2013).…”
Section: Symbolic Capital and Symbolic Violencementioning
confidence: 99%
“…In this study, student recognition of the value of work experience to them is taken to be an indication of understanding the rules of the game of graduate employment, where recognition includes attending preparatory workshops, submitting applications and attending interviews. Bourdieu developed the concept of capital, from Marxian ideas in which economic capital shapes society, to the more pluralistic, nuanced, and reflexive framework of capitals (Yamak, Ergur, Özbilgin, & Alakavuklar 2016).…”
Section: Habitus Capitals and Playing The Gamementioning
confidence: 99%
“…Bourdieu's concept of symbolic capital draws attention to the resources that support recognition of prestige, legitimacy, meaning, value and power (Navarro 2006;Yamak et al 2016). Tomlinson (2017) argues that this framework supports investigations of the myriad resources (or deficits) that may support our paths through study to working life.…”
Section: Habitus Capitals and Playing The Gamementioning
confidence: 99%
See 1 more Smart Citation